PENERAPAN METODE DISKUSI DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA SEKOLAH DASAR - Putri Maratus Sholikhah; Nur Ifan syah (CV. Denasya Smart Publisher, 2024)
Improving critical thinking skills in elementary school is an important part of education. The debate method has proven to be effective in helping students develop critical thinking skills. From the research results, it is known that elementary school students' critical thinking abilities using the discussion method have increased significantly. Students who have the opportunity to learn using the discussion method significantly improve their ability to analyze information, evaluate arguments, and make decisions. This research provides strong evidence regarding the benefits of using discussion techniques in basic education programs to improve students' critical thinking skills. Such practice implies that it is important for primary school teachers to focus on the integration of discussion techniques in everyday classes, in order to enrich students' learning experience and improve their academic performance.